Rozśpiewane przedszkole. O potrzebie zajęć umuzykalniających w codziennym wychowaniu przedszkolnym - Adamczewski, Jakub (Studia Edukacyjne, 2020)
The article presents the educational aspects of the music education in everyday preschool activities. The main idea is to widely describe the role of the music activities dedicated to the youngest. Based on the literature, I tried to connect the theory with the examples of everyday teaching practice. Each part was supported with free and accessible sources of educational materials. The role of the catholic preschool teacher was stressed as well, which is crucial for the future of Polish music education.